Extracellular electron transfer of Shewanella oneidensis MR-1 for cathodic hydrogen evolution reaction. (10th May 2019) - Fu, Yanan; Zhang, Yongjia; Li, Bojian; Liang, Dawei; Lu, Shanfu; Xiang, Yan; Xie, Beizhen; Liu, Hong; Nealson, Kenneth H.
Abstract: Electron transfer from solid electrodes to microbes through reversed extracellular electron transfer (EET) has been realized in bioelectrochemical systems (BESs), which have gained much attention in the realm of bioenergy and bioremediation. In this study, Shewanella oneidensis MR-1 was found to catalyze cathodic hydrogen evolution (HEv) at a potential of −0.758 V vs . standard hydrogen electrode (SHE) in a BES. Analysis via differential pulse voltammetry analysis revealed a strong enhancement of HEv by added nicotinamide adenine dinucleotide (NAD) but no impact by the addition of either NADH or riboflavin (RF) and flavin mononucleotide (FMN). Moreover, NADH, when added in combination with flavins inhibited cathodic EET and HEv. The mechanism by which these stimulations and inhibitions are not clear at this time. In summary, this study lays the foundation for understanding both reversed EET and hydrogen evolution catalyzed by S. oneidensis MR-1.